Salidroside alleviates high-glucose-induced injury in retinal pigment epithelial cell line ARPE-19 by down-regulation of miR-138. Issue 10 (3rd October 2019) - Qian, Cheng; Liang, Shenzhi; Wan, Guangming; Dong, Yi; Lu, Taiying; Yan, Panshi
ABSTRACT: Diabetic retinopathy (DR) is a complication of diabetes leading cause of blindness in adults. Salidroside (SAL) is a main ingredient from Rhodiola rosea L ., has been reported to have a beneficial protection on vascular function. However, whether SAL is a suitable treatment for DR remains unreported. The study aimed to investigate the effect of SAL on high-glucose (HG)-induced injury in ARPE-19 cells. ARPE-19 cells were managed with diverse concentrations of glucose, and constructed a model of HG-induced ARPE-19 cells injury. Then, SAL was employed to stimulate ARPE-19 cells, and cell viability, apoptosis, apoptosis-associated factors, the pro-inflammatory cytokines, and ROS levels were determined. The correlation between miR-138 and SIRT1 was predicated by bioinformatics software of TargetScan (http://www.targetscan.org/) and Dual luciferase reporter assay. MiR-138 mimic, inhibitor and NCs were transfected into ARPE-19 cells, and the impacts of miR-138 on HG-induced cell injury were investigated. PI3K/AKT and AMPK signalling pathways were examined to explore the underlying mechanism. The results disclosed that HG inhibited cell viability, promoted apoptosis, up-regulated IL-6 and TNF-α, as well as increased ROS level in ARPE-19 cells. But, SAL obviously alleviated HG-induced ARPE-19 cells injury. Repressed miR-138 was triggered by SAL, and SIRT1 was predicated as a direct target of miR-138. Overexpressed miR-138 declined the protective effect of SAL on HG-injured ARPE-19 cells. Besides, SAL activated PI3K/AKT and AMPK pathways by adjusting miR-138. In conclusions, SAL flattened HG-induced injury in ARPE-19 cells by repression of miR-138 and activating PI3K/AKT and AMPK pathways.